PENGARUH PEMBERIAN MOBILISASI DINI TERHADAP PEMULIHAN PERISTALTIK USUS PADA PASIEN POST OPERASI LAPARATOMI DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Sari desi Esta Ulina Sitepu; Abdi Lestari Sitepu; Pratiwi Christa Simarmata; Ria Fitri Anggrareni; Selamat Tuahta Sipayung (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2021)
Surgery is performed by taking certain body parts, with the aim of improving the body that has abnormalities such as laparotomy. This action can disable the sound of the prism with the state of the body that is anesthetized. Early mobilization is one of the effective ways to re-stimulate bowel function and produce normal peristaltic sounds and patients can be selected. The purpose of this study was to determine the effect of early mobilization on the recovery of intestinal peristalsis in post-laparatomy patients at Grandmed Lubuk Pakam Hospital. This study used a one-group pretest-posttest design, with pre-experimental pre-test (early stage) and post-test (final stage) with a sample of 27 respondents while the research instrument used an observation sheet. Data analysis used bivariate analysis, namely the Paired Sample T-Test. The results of the bivariate test with Paired Sample T-Test proved that there was an effect of early mobilization on increasing intestinal peristalsis before and after the procedure, as evidenced by the p-value = 0.00 < 0.05. As early as possible, early mobilization doing in post-laparatomy patients, the faster the intestinal peristaltis recovery process will be.